Control of cystic fibrosis transmembrane conductance regulator membrane trafficking: not just from the endoplasmic reticulum to the Golgi - Farinha, Carlos (2014)
Biogenesis of cystic fibrosis transmembrane conductance regulator (CFTR) starts with its cotranslational insertion into the membrane of the endoplasmic reticulum (ER) and core glycosylation. These initial events are followed by a complex succession of steps with the main goal of checking the overall quality of CFTR conformation in order to promote its exit from the ER through the secretory pathway. Failure to pass the various checkpoints of the ER quality control targets the most frequent disease-causing mutant protein (F508del-CFTR) for premature degradation. For wild-type CFTR that exits the ER, trafficking through the Golgi is the major site for glycan processing, although nonconventional trafficking pathways have also been described for CFTR. Once CFTR is at the cell surface, its stability is also controlled by multiple protein interactors, including Rab proteins, Rho small GTPases, and PDZ proteins. These regulate not only anterograde trafficking to the cell surface, but also endocytosis and recycling, thus achieving fine and tight modulation of CFTR plasma membrane levels. Exciting recent data have related autophagy and epithelial differentiation to the regulation of CFTR trafficking. Herein, we review the various checkpoints of the complex quality control along the secretory trafficking pathway and the associated pathways that are starting to be explored for the benefit of cystic fibrosis patients.